Chalcone synthase cosuppression phenotypes in petunia flowers: comparison of sense vs. antisense constructs and single-copy vs. complex T-DNA sequences - Jorgensen, R.A. (California Univ., Davis, CA (USA). Dept. of Environmental Horticulture); Cluster, P.D; English, J; Que, Q; Napoli, C.A (Plant molecular biology, 1996)
Flower pigmentation patterns were scored in 185 sense Chalcone synthase (Chs) transgenotes and 85 antisense Chs transgenotes; upon first flowering, 139 (75%) of sense transgenotes were found to be phenotypically altered, as were 70 (82%) of the antisense transgenotes. The observed patterns document the range of phenotypic variations that occur, as well as confirm and extend the finding that sense Chs constructs produce several types of morphology-based flower pigmentation patterns that antisense Chs constructs do not. Long-term monitoring for epigenetic variations in one population of 44 sense Chs transgenotes showed that 43 (98%) were capable of producing a cosuppression phenotype. The primary determinant of sense-specific patterns of cosuppression of Chs was found to be the repetitiveness and organization pattern of the transgene, not 'position effects' by, or 'readthrough' from, flanking plant DNA sequences. The degree of cosuppression observed in progeny of transgenotes carrying multiple, dispersed copies as compared to that observed with a single copy of the transgene suggests that sense cosuppression of Chs is subject to a transgene dosage effect.